Different fractions of human serum glycoproteins bind galectin-1 or galectin-8, and their ratio may provide a refined biomarker for pathophysiological conditions in cancer and inflammatory disease - Carlsson, Michael C.; Balog, Crina I.A.; Kilsgård, Ola; Hellmark, Thomas; Bakoush, Omran; Segelmark, Mårten; Fernö, Mårten; Olsson, Håkan; Malmström, Johan; Wuhrer, Manfred; Leffler, Hakon (Biochimica et biophysica acta, 2012)
Changes in glycosylation of serum proteins are common, and various glycoforms are being explored as biomarkers in cancer and inflammation. We recently showed that glycoforms detected by endogenous galectins not only provide potential biomarkers, but also have different functions when they encounter galectins in tissue cells. Now we have explored the use of a combination of two galectins with different specificities, to further increase biomarker sensitivity and specificity. Sera from 14 women with metastatic breast cancer, 12 healthy controls, 14 patients with IgA-nephritis (IgAN), and 12 patients with other glomerulonephritis were fractionated by affinity chromatography on immobilized human galectin-1 or galectin-8N, and the protein amounts of the bound and unbound fractions for each galectin were determined. Each galectin bound largely different fractions of the serum glycoproteins, including different glycoforms of haptoglobin. In the cancer sera, the level of galectin-1 bound glycoproteins was higher and galectin-8N bound glycoproteins lower compared to the other patients groups, whereas in IgAN sera the level of galectin-8N bound glycoproteins were higher. The ratio of galectin-1 bound/galectin-8N bound glycoproteins showed high discriminatory power between cancer patients and healthy, with AUC of 0.98 in ROC analysis, and thus provides an interesting novel cancer biomarker candidate. The galectin-binding ability of a glycoprotein is not only a promising biomarker candidate but may also have a specific function when the glycoprotein encounters the galectin in tissue cells, and thus be related to the pathophysiological state of the patient. This article is part of a Special Issue entitled Glycoproteomics. [Display omitted] ► Glycoforms of human serum proteins were detected using lectins, galectin-1 and -8N. ► The two galectins bound different sets of glycoforms by affinity chromatography. ► Galectin-1 bound glycoforms increased and galectin-8N bound decreased in cancer. ► The reverse was true in inflammatory kidney disease (IgA-nephropathy). ► The ratio segregated cancer patients from others with AUC 0.98 in an ROC plot.